Going Concern Matter Disclosure: Evidence from Abnormal Cash Flow, Value Creation, Litigation, and Governance - Dela Ameliasari; Nanik Sri Utaminingsih (Politeknik Ganesha Medan, 2026)
Going Concern represents a fundamental assumption underlying the preparation of financial statements, and is a key focus in the audit process, especially with the existence of SA 570 Revision 2021, which requires the disclosure of material uncertainty through going concern matter disclosure (GCMD). This study investigates the influence of abnormal operating cash flow, value creation, litigation, and audit committee on GCMD in the audit reports of consumer cyclicals companies. The research population includes all consumer cyclicals companies listed on the Indonesia Stock Exchange for the period 2022–2024. Purposive sampling was used to obtain 71 companies with a total of 213 observations as the research analysis units. A quantitative approach with causal research design was applied. Secondary data were obtained from annual reports and independent auditor reports published on the official website of the Indonesia Stock Exchange. Logistic regression analysis was employed to examine the effect of each independent variable on the probability of GCMD disclosure. The findings reveal that litigation risk and value creation have a positive and significant effect on GCMD disclosure, whereas the audit committee shows a significant negative relationship. In contrast, abnormal operating cash flow does not significantly influence GCMD. These results suggest that auditors place greater emphasis on legal risk exposure, governance effectiveness, and uncertainty surrounding future value generation rather than relying solely on operational cash flow indicators when assessing business continuity.